Settlement Of Defaults In Endorsement Agreements Between Business Owners And Selebgram As Online Promotion Media Instagram In Malang City Perspective Civil Code Of Law And Compilation Of Sharia Economic Law - Fina As'ada (Fakultas Syariah Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
Online-based trading is increasingly being used by business people as a strategy in marketing their products by using celebrity services as outlined in the endorsement agreement. In addition to being profitable, there are problems in implementing the agreement, the problems that occur are, there are parties that do not fulfill obligations in accordance with the initial agreement, causing losses to one of the parties called default. Such is the case of default conducted by celebrities to online business owners at Monochromestore Malang online shops and several online business owners in Malang City. This study aims to examine how the settlement of defaults in the endorsement agreement between the business owner and the perspective program of the Civil Code and the Compilation of Sharia Economic Laws. This research uses a type of empirical legal research, using a sociological juridical approach as well as data collection using interviews and documentation studies. The result of the research is first, the implementation of endorsement agreement is done through direct message with instagram account, whatsapp, or contact the contact listed on the data selebgram to be invited to cooperate. Second, the settlement of default in the Civil Code is regulated in article 1243 that “compensation for costs, losses and interest due to non-fulfillment of an engagement is mandatory”. Third, settlement of Default (broken promise) according to the Compilation of Sharia Economic Laws is contained in article 36, parties who have broken their promises can be subject to sanctions: paying compensation, canceling the contract, transferring risks, fines and paying court fees.